Are there biases in the market definition procedure? - Markku Stenborg (The Research Institute of the Finnish Economy (ETLA), 2004)
Indirect analysis of market power requires market delineation. Procedures in competition case law can be biased, as sample of market participants is typically biased or wrong one for analysis of market boundaries. Market delination can then be biased to too narrow markets, thus finding too much market power. As a remedy, analysis should concentrate on marginal, not infra-marginal customers, and use and understand economic tools such as demand elasticity and direct estimation of market power, if possible.
Keywords: L40; K21; 330; market delineation; competition policy; SSNIP-test; demand elasticity; Relevanter Markt; Bias; Theorie